Kathryn Dyt. The Nature of Kingship: The Weather-World in Nineteenth-Century Vietnam. Honolulu: University of Hawai‘i Press, 2025. - Thompson, C. Michele (Southeast Asian Studies, 2026)
Keywords: book.review; dept.his

British first world war propaganda: from A to Z - Paddock, Troy (First World War Studies, 2026)
Keywords: dept.his

Melissa Reynolds. Reading Practice: The Pursuit of Natural Knowledge from Manuscript to Print - Petto, Christine (The American Historical Review, 2025)
Keywords: Knowledge production; Knowledge-based systems; Natural (archaeology); Traditional knowledge; dept.his

Meredith L. McCoy. On Our Own Terms: Indigenous Histories of School Funding and Policy - Amerman, Steve (The American Historical Review, 2025)
Keywords: Indigenous; Indigenous culture; dept.his

Bamboo in Vietnam: an anthropological and historical approach, written by ðinh Trọng Hiếu and Emmanuel Poisson - Thompson, C. (East Asian Science Technology and Medicine, 2025)
Keywords: Ancient history; Anthropology; Archaeology; Asian studies; Bamboo; Biology; Botany; China; History; Medicine; Sociology; Traditional medicine; dept.his

Finding the Sweet Spot: Wild Bees, Indigenous Peoples, and the Historic Trade in Honey and Beeswax in Northern Vietnam - Thompson, C. Michele (Asian Medicine, 2026)
When most people think of the use of animals in traditional systems of medicine, what springs to mind is one kind or another of megafauna such as rhinoceros, bears, sharks, and others. Sometimes more mundane creatures such as pangolins are included. However, invertebrates and substances produced by them have been used in Asian systems of medicine since the earliest records of materia medica from the region were created. Animals used range from shellfish and crustaceans to various insects and insect products such as cocoons, honey, and beeswax. In terms of their role in the food chain, and as pollinators, invertebrates are as crucial to the health, indeed the survival, of ecosystems in Asia and elsewhere as are megafauna. Loss and degradation of habitat is probably affecting more invertebrates than medicalization. Still, the expansion of medicalization in Asia and beyond is contributing to the danger many populations of invertebrates currently face. This article gives an overview of the place of invertebrates in Vietnamese traditional medicine and then presents a case study of two varieties of honey- and beeswax-producing bees found in northern mainland Southeast Asia and southern China: Apis dorsata F. and Apis cerana. © C. Michele Thompson, 2026. Published with license by Koninklijke Brill BV
Keywords: Arthropod; Asian traditional medicine; Creatures; Habitat; Invertebrate; Mainland; Mainland China; Southeast asia; Vietnamese; Vietnamese medicine; bees; beeswax; dept.his; ecological damage; endangered species; honey; invertebrates

‘A small measure of fairness’: Black South Africans and the Courts, 1919–1938 - Eastman, Michael; Feinberg, Harvey (Journal of Southern African Studies, 2025)
Keywords: Computer science; Measure (data warehouse); Political science; Sociology; South Africa; administration of justice; appeals; courts; criminal justice; dept.his; judges; justice for Africans; magistrates; reviews

Defining the enemy: Propaganda in a civil war - Paddock, Troy (Violence and Propaganda in European Civil Wars, 2025)
Propaganda in the first half of the 20th century is usually associated with the atrocity stories from World War I and the anti-Semitic propaganda of the Nazi regime and World War II. This chapter provides a brief overview of the history of propaganda and propaganda theory before turning its attention to a theory of propaganda in civil war. It argues that what makes propaganda in a civil war unique is that it is a combination of both political and war propaganda. Current research on propaganda theory emphasizes that propaganda is in service of an ideology and focuses on propaganda as disseminating information that tries to avoid reason and veracity. The chapter argues that propagandists in a civil war setting are presenting the ‘truth’ as they understand it. Informed by Carl Schmitt’s “friend/enemy” distinction in his Concept of the Political, the author argues that each side argued and was convinced that they represented the values and interests of the nation and its people, and that because the stakes of the conflict were so high that all actions could be justified.
Num Pages: 11
Keywords: dept.his

Changing Working Environments in Philosophy: Reflections from a Case Study - McConwell, Alison; Bogacz, Magdalena; Brecevic, Char; Haber, Matthew; Wu, Jingyi; Roe, Sarah (Philosophy of Science, 2025)
Abstract There is an “underrepresentation problem” in philosophy departments and journals. Empirical data suggest that while we have seen some improvements since the 1990s, the rate of change has slowed down. Some posit that philosophy has disciplinary norms making it uniquely resistant to change. We present results from an empirical case study of a philosophy department that achieved and maintained male-female gender parity among its faculty as early as 2014. Our analysis extends beyond matters of gender parity because that is only one, albeit important, dimension of inclusion. We build from the study to reflect on strategies that may catalyze change.
Keywords: Computer science; Epistemology; Philosophy; Sociology; dept.his; peer-reviewed

How the west was run: Local government in Late Roman Italy - McCunn, Stuart (Late Roman Italy: Imperium to Regnum, 2023)
h4Explores the major political, social, economic, religious and cultural changes impacting what was once the most important region of the Roman world/h4ulliThe first modern research volume on a core region of Late Antiquity/liliA tight and distinctly chronological focus on the second quarter of the first millennium CE, that allows for a different vision of the many vicissitudes of Late Roman Italy, among other works on Ancient and Late Antique Italy./liliAn emphasis on one of the key features of Late Antiquity: the transformation of the Roman Empire in the West into successor polities./liliA balanced range of topics, including ones rarely encountered in this type of work (such as gender or environmental history), with a special focus on political transformation and violence./li/ulpThis research volume reassesses one of the most fundamental transformations in Late Antiquity, centered on a pivotal region: the transition from ‘Empire’ to ‘Kingdom’ in Italy c. 250-500. During the first quarter of the first millennium, Italy was still the heart of the Roman Empire; the only political superstructure ever managing to encompass the entire Mediterranean world and its European hinterland. Yet during the second quarter of this millennium, Italy underwent dramatic evolutions from demotion to a provincialized region (c. 285-395), to a new imperial hub kept afloat by cannibalizing other provinces’ resources (c. 395-476), to an autonomous regnum governed by non-Roman rulers as part of an Eastern Roman ‘Commonwealth’ (c. 475-535)./p
Keywords: dept.his

Community and identity in Castilian histories of the fifteenth century - Kern, Darcy (Sharq al-Andalus, 2021)
La historia fue tan importante para la construcción de la identidad comunitaria y la legitimidad política en el siglo XV como lo es hoy, y en los reinos de España igualmente tenso. Los cronistas y biógrafos católicos castellanos parecen inseguros del estado preciso de los moros en Iberia. Todos estaban de acuerdo con el control político o el señorío de los cristianos castellanos, pero pocos tenían una idea clara de las implicaciones de ese señorío para los moros. ¿Debería permitirse a los moros permanecer como parte de la comunidad una vez que un monarca cristiano castellano tomara el control de su ciudad, región o reino, o no había posibilidad de que pertenecieran? Rodrigo Sánchez de Arévalo (1404-1470), Fernán Pérez de Guzmán (c. 1377-c. 1460), Alonso Fernández de Palencia (1423-1492), Hernando de Pulgar (1436-c. 1492), y Mosén Diego de Valera (1412-1488) dieron diferentes respuestas. Todos coincidieron en que la comunidad castellano-leonesa existía antes de al-Andalus y, por lo tanto, era la comunidad política legítima de Hispania. La mayoría de ellos aceptaron la presencia de Granada de facto pero no de jure. Sin embargo, Arévalo, Valera y Pulgar sugieren la posibilidad de una comunidad política musulmana de jure bajo dominio castellano; Palencia y Guzmán no.
Accepted: 2021-07-14T06:58:23Z
Keywords: dept.his

Ritual performance in early Chinese thought: A dramaturgical perspective - Radice, T. (2024)
Examining early Chinese ritual discourse during the Warring States and early Western Han Periods, this book reveals how performance became a fundamental feature of ritual and politics in early China. Through a dramaturgical lens, Thomas Radice explores the extent to which performer/spectator relationships influenced all aspects of early Chinese religious, ethical, and political discourse. Arguing that the Confucians conceived ritual as primarily a dramaturgical matter, this book demonstrates not only that theatricality was necessary for expression and deception in a community of spectators, but also how a theatrical 'presence' ultimately became essential to all forms of public life in early China. Thomas Radice illuminates previously unexplored connections between early Chinese texts, aesthetics, and traditions. © Thomas Radice, 2025. All rights reserved.
Pages: 180
Keywords: dept.his

Englishing Paolo Sarpi and gelding the Pope in England, 1606−1620 - Kern, Darcy (The Seventeenth Century, 2024)
An important reason for the success of the Venetian Paolo Sarpi’s ideas in England is found in the ‘Englishing’ of his printed works, that is, their adaptation and appropriation by printers and translators. During the Venetian interdict (c. 1606–1608), Sarpi’s tracts were treated as timely, informative, and politically useful news. Englishing consisted of re-writing titles by adding bombastic phrases, changing printers’ ornaments, and adding marginalia to help readers unfamiliar with Italy. In the History of the Council of Trent, published in 1619 (Italian) and 1620 (English), the Englishing became more substantive – adding lengthy prefaces, inserting words into Sarpi’s text, and including the translator’s name. The prefaces framed the book’s contents, while the translator’s name provided authority. The additional words made the English History even more partisan than the Italian Historia. Publishers and translators modified Sarpi’s works to produce aggressive readings that diverged from his own political and religious goals.
_eprint: https://doi.org/10.1080/0268117X.2024.2389546
Keywords: Catholic Church; Church of England; England; Translation; Venice; dept.his; peer-reviewed; print culture

Receiving more: Utopia in Spain and new Spain - Kern, D. (The Oxford Handbook of Thomas More's Utopia, 2023)
Keywords: dept.his

Book Review: Aro Velmet, Pasteur’s Empire: Bacteriology & Politics in France, Its Colonies, & the World (New York: Oxford University Press, 2020), pp. xiv + 306, $78.00, hardback, ISBN: 9780190072827. - Thompson, C. Michele (Medical History, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0025727321000508/resource/name/firstPage-S0025727321000508a.jpg
Keywords: dept.his

Book Review: Edington, Claire E. – Beyond the Asylum: Mental Illness in French Colonial Vietnam. - Thompson, C. Michele (Histoire sociale / Social History, 2023)
Number: 115
Keywords: book.review; dept.his

Book Review: Epidemic Politics in Contemporary Vietnam: Public Health and the State By Martha Lincoln, London: Bloomsbury Academic. 2022. 232 pp.1 - Thompson, C. Michele (Medical Anthropology Quarterly, 2024)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/maq.12840
Keywords: book.review; dept.his

Book Review: Fragrant Frontier: Global Spice Entanglements from the Sino-Vietnamese Uplands - Thompson, C. Michele (Agricultural History, 2024)
The editors of Fragrant Frontier have produced an impressively researched book on the contemporary growers, in northern Vietnam and Southwest China, of three spices—star anise, black cardamom, and cinnamon, each of which has local, regional, and international economic importance—as well as the human links in the global commodity chain of these spices. This volume is much more coherent than many edited volumes, and readers should not skip any of it, as there are nice little surprises waiting here and there in the text.A good example is the “Preface and Acknowledgements” section, as this not only provides interesting information on how the volume came into being but also links to websites and scannable QR codes for “story maps” on the three spices and the places mentioned in the rest of the volume. This is a nice touch that gives this volume about the recent situation of farmers, local traders, marketplace workers, street vendors (of both the spices and foods prepared with them), wholesalers, exporters, and state officials a very contemporary feel. These story maps are only the first of an extensive number of relevant, well-done, and well-used illustrations including photographs, maps, and tables inserted throughout the following chapters.
Keywords: book.review; dept.his

Fighting for health: medicine in cold war Southeast Asia - Thompson, Claudia Michele; Sweet, Kathryn; Aso, Michitake (NUS Press, 2024)
Keywords: 20th century; Cold War; Medicine; 20th century; Medical care; 20th century; Medical policy; History; History; Public Health; Public health; Southeast Asia; dept.his; history; Health Policy; history; History of Medicine; Southeast Asia; Asia; Southeastern

The Duke of Lennox, 1574 1624: A Jacobean Courtier s Life. David Bergeron. Edinburgh: Edinburgh University Press, 2022. x + 244 pp. $110 - Kern, Darcy (Renaissance Quarterly, 2023)
Keywords: book.review; dept.his

The many currents of antebellum maritime empire - Smith, Jason W. (Diplomatic History, 2023)
Keywords: dept.his; peer-reviewed

Costa Rica after Coffee: The Co-op Era in History and Memory - Kordick, Carmen (Agricultural History, 2023)
Num Pages: 3
Keywords: book.review; dept.his

Al-Ḥağğāğ b. Yūsuf and the Umayyad Qurʾān in Syrian Historiography - Judd, Steven C. (Archimède. Archéologie et histoire ancienne, 2023)
Num Pages: 11
Keywords: dept.his; peer-reviewed

Aspects of Greek-Russian Relations in the Early Modern and Modern Periods (17th-20th Centuries) - Chrissidis, Nikolaos (Annuaire de l'École pratique des hautes études (EPHE), Section des sciences religieuses. Résumé des conférences et travaux, 2023)
This series of four presentations sought to examine case studies of Greek-Russian relations in the early modern and, mostly, modern period. In the choice of topics, I was guided by two considerations: first, I sought to highlight topics that, to my mind, have not yet attracted the attention they deserve in historiography. For example, although alms collections in the Russian Empire in the early modern period have been discussed repeatedly, this has not been the case until quite recently for t...
ISBN: 9782909036519 Number: 130
Keywords: Christianisme orthodoxe; Histoire des chrétiens d’Orient (XVIe-XXIe siècle); dept.his

Russia in the German global imaginary: imperial visions and utopian desires, 1905-1941 - Paddock, Troy (First World War Studies, 2023)
Num Pages: 2
Keywords: book.review; dept.his

Review of Chivalry and Violence in Late Medieval Castile, by Samuel A. Claussen - Kern, Darcy (Journal of Military History, 2022)
Keywords: book.review; dept.his; ⛔ No DOI found

al-Awza'i and Umayyad Influence on Islamic Legal Development - Judd, Steven (The Umayyad World, 2020)
The Umayyad World encompasses the archaeology, history, art, and architecture of the Umayyad era (644–750 CE). This era was formative both for world history and for the history of Islam. Subjects covered in detail in this collection include regions conquered in Umayyad times, ethnic and religious identity among the conquerors, political thought and culture, administration and the law, art and architecture, the history of religion, pilgrimage and the Qur’an, and violence and rebellion. Close attention is paid to new methods of analysis and interpretation, including source critical studies of the historiography and inter-disciplinary approaches combining literary sources and material evidence. Scholars of Islamic history, archaeologists, and researchers interested in the Umayyad Caliphate, its context, and infl uence on the wider world, will find much to enjoy in this volume.
Keywords: dept.his

Siyar: An Ephemeral Genre of Islamic Legal Literature? - Judd, Steven (Islam on the Margins, 2022)
Section: Islam on the Margins
Keywords: History & Culture; Middle East and Islamic Studies; Religion in Asia; Religious Studies; dept.his

Islam on the Margins: Studies in Memory of Michael Bonner - Judd, Steven; Haug, Robert (BRILL, 2023)
Islam on the Margins commemorates the contributions Michael Bonner made to Near Eastern Studies. It consists of fourteen contributions by his students and colleagues that focus on various aspects of his work. The contributions coalesce around four major themes of Bonner’s endeavours: Holy War and the Frontier, Qurʾan and Law, Geography and Ethnography, and Books, Coins and Titles. Collectively, the contributions underscore the breadth of Michael Bonner’s erudition and impact on the field.
Google-Books-ID: JQqtEAAAQBAJ
Keywords: History / Asia / General; History / Middle East / General; Religion / Islam / General; dept.his

The Cassock Does Not a Monk Make. Or Does It? Fake and Real Monks from the Orthodox East in the Russian Empire (19th — Early 20th Сentury) - Chrissidis, Nikolaos (Istoriya, 2023)
Monastic tonsure of citizens of the Russian Empire abroad became a particularly complex issue during the latter half of the nineteenth century, when Mt. Athos became a favorite destination of those interested in assuming the monastic habit outside the empire. The Russian authorities sought to control and regulate such tonsures by establishing procedures for checking their validity, and by ruling out automatic recognition of them in the empire. Individuals who were tonsured as monks abroad manipulated or tried to manipulate such regulations in order to facilitate travel back and forth from the Russian Empire for their own purposes. The result was that the real and apparent ambiguities that such rules allowed for were exploited by both state authorities and by real or fake monks themselves. The essay seeks to offer some perspectives on this phenomenon by focusing on four cases preserved in archival records. © 2023 Ltd "Integration: Education and Science". All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: Mount Athos; St. Panteleimon Monastery; dept.his; fake monks; monasticism; peer-reviewed; tonsures abroad

The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. By HANNAH-LENA HAGEMANN. Edinburgh: EDINBURGH UNIVERSITY PRESS, 2021. Pp. xii + 316. $110, £85 - Judd, Steven C. (Journal of the American Oriental Society, 2023)
0 citations (Crossref) [2023-10-31]
Keywords: book.review; dept.his

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge/Taylor & Francis Group, 2020)
Keywords: Causes; Historiography; Historiography; World War; 1914-1918; World War; 1914-1918; dept.his; faculty_collection

Western Science in Indochina, 1800-1998 - Thompson, C Michele (The Cambridge History of Science Vol. 8, Modern Science in National and International Context, 2020)
Keywords: dept.his

A Narrative That Was Not Her Own: Mary I as Mediterranean Queen - Kern, Darcy (Writing Mary I: History, Historiography, and Fiction, 2022)
Nearly every biography of Mary Tudor mentions her acquisition of the Kingdom of Naples and the Spanish kingdoms through her marriage to Philip Habsburg, later Philip II of Spain, but they say little about her role as queen consort, primarily because she failed to control the narrative of her reign. She made little effort to patronize writers, disperse her symbols, send images of herself, use masculine terminology like her grandmother Isabel of Castile, or involve herself in the governance of her Mediterranean kingdoms. Her real and symbolic absence in the south, and the presence of Doña Juana, Philip’s sister and the capable regent of the Spanish kingdoms in his absence, led to her marginalization. This has had long-lasting consequences for the historiography of her reign, as historians have generally confined themselves to studying her in her English context using the gendered language of early Spanish writers while omitting her entirely from Naples.
Keywords: award_winner; dept.his

A dramaturgy of death: Performing (and spectating) filial piety in early china - Radice, T. (Journal of Chinese History, 2022)
This essay analyzes the early Chinese elite discourse on filial death rituals, arguing that early Chinese texts depict these rituals as performance events. Building on spectacle of xiao sacrifices in the Western Zhou Dynasty, Eastern Zhou authors conceived of filial death rituals as dramaturgical phenomena that underscored not only what needed to be performed, but also how it should be performed, and led to an important distinction between personal dispositions and inherited ritual protocol. This distinction, then, led to concerns about artifice in human behavior, both inside and outside the Ruist (Confucian) tradition. By end of the Warring States Period and in the early Western Han Dynasty, with the embracement of artifice in self-cultivation, the dramatic role of the filial son in death rituals became even more developed and complex, requiring the role of cultivated spectators to be engaged critics who recognized the nuances of cultivated performances. Copyright © The Author(s), 2021. Published by Cambridge University Press.
0 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85118183872
Keywords: dept.his; peer-reviewed

Book Review: The keepers of the seas the blue age gregg easterbrook PublicAffairs, 2021. 304 pp. - Smith, Jason W. (Science (New York, N.Y.), 2021)
0 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/34516783
Keywords: article; book.review; dept.his

Understanding the role of wrongdoing in technological disasters: Utilizing ecofeminist philosophy to examine commemoration. - Roe, Sarah M.; Zavar, Elyse (Studies in history and philosophy of science, 2021)
Stemming from human accident, error, or neglect, technological disasters, such as chemical spills, toxic waste contamination, nuclear radiation, transportation accidents, and factory explosions, are products of the modern industrial complex. Toxic contamination of the land can permanently displace people from their homes and erase places from the landscape. Commemoration provides an opportunity to remember the past and celebrate culturally significant place attachments while contributing to the recovery process by aiding in community healing after devastating events. We focus on two key components regarding commemoration after technological disaster, namely the acknowledgement of wrongdoing and the celebration of a resilient population and landscape. We argue that a combination of ecofeminist philosophy and environmental justice frameworks allows for a better understanding of the cycle of disaster and mitigation as it pertains to targeted groups, and that commemorative acts and artifacts following human-made disasters often fail to successfully reform this cycle. Moreover, the combination of ecofeminist philosophy and environmental justice allows us to examine the complex relationship between responsibility and targeted groups through disaster commemoration, which serves as an important way to communicate wrongdoing to both the local and greater population. Through engagement with ecofeminist philosophy and environmental justice frameworks, we explicate how commemoration after technological disaster can disrupt or reinforce systematic inequalities. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31] http://www.ncbi.nlm.nih.gov/pubmed/34111819 ; https://europepmc.org/article/MED/34111819 ; https://philpapers.org/rec/ROEUTR ; https://www.ncbi.nlm.nih.gov/pubmed/34111819
Keywords: article; artifact; contamination; dept.his; disaster; explosion; factory; human; justice; neglect; peer-reviewed; philosophy; responsibility; toxic waste

Storm of the Sea: Indians & Empires in the Atlantic's Age of Sail - Smith, Jason W. (Journal of American Studies, 2020)
0 citations (Crossref) [2023-10-31] WOS:000570682600011
Keywords: dept.his; peer-reviewed

Preserving Maritime America: A Cultural History of the Nation's Great Maritime Museums - Smith, Jason W. (New England Quarterly-a Historical Review of New England Life and Letters, 2020)
0 citations (Crossref) [2023-10-31] WOS:000565265800019
Keywords: dept.his

Guatemala's Catholic Revolution: A History of Religious and Social Reform, 1920-1968. - Kordick, Carmen (Americas, 2020)
0 citations (Crossref) [2023-10-31] WOS:000529165900022
Keywords: dept.his; peer-reviewed

They're going to kill me there. Culture, violence and the Cold War in Costa Rica (1979-1990) - Kordick, Carmen (Americas, 2020)
0 citations (Crossref) [2023-10-31] WOS:000509713100024
Keywords: dept.his; peer-reviewed

Indochina - Thompson, C. Michele (Cambridge History of Science, Vol 8: Modern Science in National, Transnational, and Global Context, 2020)
WOS:000548448800032
Keywords: dept.his

Notes on the state of Virginia: an annotated edition - Jefferson, Thomas; Forbes, Robert Pierce (Yale University Press, 2021)
Keywords: Description and travel; Early works to 1800; Early works to 1800; Virginia; History; Virginia; dept.his; faculty_collection

The Rumble in the Jungle: Muhammad Ali and George Foreman on the Global Stage - Rondinone, Troy (Journal of American History, 2020)
0 citations (Crossref) [2023-10-31] WOS:000584507900131
Keywords: dept.his; peer-reviewed

The russian holy synod and the greeks: Reconsidering greek-russian relations in the early modern period (16th–18th centuries) - Chrissidis, Nikolaos A. (Canadian-American Slavic Studies, 2020)
The article first surveys Greek interpretations of the creation of the Russian Holy Synod by Peter the Great. It provides a critical assessment of the historiographical paradigm offered by N.F. Kapterev for the analysis of Greek-Russian relations in the early modern period. Finally, it proposes that scholars should focus on a Greek history of Greek-Russian relations as a complement and possibly corrective to the Kapterev paradigm. © verlag ferdinand schöningh, 2020.
1 citations (Crossref) [2023-10-31] tex.ids: chrissidisRussianHolySynod2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85092349515 type: Article
Keywords: Aleksander stourdza; Greek-russian relations; Konstantin oinonomos; Nikolai kapterev; Peter the great; Russian holy synod; dept.his; peer-reviewed

The threat from the east - Paddock, Troy (The Central Powers in Russia's Great War and Revolution, 1914-22: enemy visions and encounters, 2020)
"This multiauthor collection of essays analyzes Russia's Great War and Revolution from the perspective of the Central Powers and their encounters with Russia and the Revolution. The peoples of the Central Powers, from elites to civilians, understood the violent clash of armies in a variety of ways. Essays highlight the variety of military and civilian experiences and deal with topics of how soldiers, civilians, and intellectuals perceived Russia and how these understandings translated into security goals, utopian plans for conquered territories, and interethnic violence."–
Keywords: 1894-1917; 20th century; Central Powers (1914-1918); Europe; Eastern; Historiography; History; History; Military; Politics and government; Revolution; 1917-1921; Russia; Soviet Union; World War; 1914-1918; dept.his